The Relationship Between Tendencies in the Development of Emotional Burnout Syndrome and Personality Accentuation in Emergency-Related Activities (a Case Study of Emergency Physicians, Rescuers and Military Sappers) - Vardanyan, Aida (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
A stable moral and psychological state of a specialist operating under conditions involving emergency situations constitutes a key prerequisite for effective professional performance. Finding oneself in emergency conditions is a major psycho-emotional factor for a specialist, which contains elements of risk to his or her life. It has a fairly strong effect on a person's body and psychological system, forcing them to adapt to the rapidly changing conditions of life.               Over time, these specialists develop the necessary psychological qualities associated with moral, psychological, and physical burdens, which in turn determine the effectiveness of overcoming work-related difficulties. At the same time, prolonged stress and high levels of responsibility may contribute to the depletion of emotional resources, a decline in professional motivation, and the development of burnout syndrome.               From an applied perspective, special importance has been given to the relationship between burnout syndrome and personality accentuation for the purpose of maintaining specialists’ psychological health and identifying risk groups. Certain types of personality accentuations may function both as protective factors and as vulnerability-enhancing factors, shaping the specific patterns of response to stressful situations. The findings of the study may serve as a basis for the development of preventive programs, the refinement of tools for assessing professional and psychological suitability, and the enhancement of professional effectiveness. The scientific analysis of this issue is important not only at the theoretical level but also at the practical level, contributing to the maintenance of psychological well-being among specialists operating under emergency conditions.
Keywords: Personality accentuation; emotional burnout syndrome; psychological overload; emotional resources; stress resilience